Effects of sulfentrazone in weed control and phytotoxicity in eucalyptus plants - Ribeiro, Luis Felipe Oliveira; Ribeiro, Jackson Roberto Dias; Almeida, Antônio Miguel Harkbart de; Ribeiro, João Victor Oliveira; Freitas, Ismael Lourenço de Jesus; Vitória, Edney Leandro da (Brazilian Journal of Production Engineering, 2026)
Chemical weed control is considered one of the costliest practices in eucalyptus silviculture, causing numerous direct and indirect impacts on crop development. Furthermore, overestimated herbicide doses and application rates can reduce application efficiency and compromise product effectiveness on the intended target. This study aimed to evaluate the efficacy of sulfentrazone applied at different doses and spray volumes in pre-emergence weed control, as well as to investigate the phytotoxicity caused to Eucalyptus grandis × Eucalyptus urophylla clones during the initial growth stage. The experimental area was established with the E. grandis × E. urophylla clone. The experiment was conducted in a randomized complete block design using a 2 × 5 + 2 factorial arrangement, consisting of two application rates (150 and 200 L ha⁻¹) and five sulfentrazone doses (400, 500, 600, 700, and 800 g ha⁻¹), plus an additional treatment with flumioxazin (standard treatment) and another treatment without herbicide application (control), with four replications. The results showed that the highest sulfentrazone dose (800 g ha⁻¹) caused the greatest phytotoxicity in eucalyptus plants. Application rates did not significantly affect weed control. Sulfentrazone doses ranging from 400 to 600 g ha⁻¹ can be used as a pre-emergence herbicide during the initial establishment phase of eucalyptus plantations
Keywords: Eucalyptus spp.; Application technology; Herbicidology